Digitalisasi Bisnis Dengan Pendekatan Solusi Mobile: Meningkatkan Keberlanjutan Dan Daya Saing Usaha pada Koperasi Konsumen Politeknik Negeri Bengkalis - Muhammad Arif; Fachroh Fiddin; Nur Rahmani; wahyu triyono (P3M Politeknik Negeri Bengkalis, 2025)
The objective of this community service activity is to assist the Politeknik Negeri Bengkalis Consumer Cooperative in implementing business process digitalization through the development and use of a mobile application solution. The Cooperative still runs its operations manually, which results in limitations in financial recording, stock management, and product promotion.The main output of this activity is the handover of one unit of a digital cash register complete with supporting devices (an Android tablet and a receipt printer) as well as training on the use of the Kasir Pintar application. The achieved impact is an increase in the understanding and digital skills of the cooperative management in utilizing digital technology. It is expected that this digitalization will enhance operational efficiency, expand market reach, strengthen business competitiveness, and serve as an initial foundation for sustainable digital transformation